Experiential Learning Overview of Millennial Women Entrepreneurs Firsta Collection (Phenomenological Study of Women Who Resign to Work as Corporate Secretary) - Nadila, Yusi; Yanladila Yeltas Putra (Causalita, 2024)
This research aims to comprehensively describe the experiential learning of millennial women entrepreneurs who decided to start a business after resigning from work to prioritize family. Through an understanding of experiential learning, an entrepreneur, especially a woman, can gain knowledge of the role of experiential learning in starting, managing and developing entrepreneurship. In an effort to achieve this research objective, a qualitative study was conducted using a phenomenological method on participants selected purposively, namely millennial businesswomen with bachelor's degrees who resigned from work for the sake of their families. The data collection techniques in this research are interviews with analysis techniques and data validity in accordance with the techniques developed by Miles, Huberman and Saldana. The results of this research are to obtain a picture related to experiential learning which can be seen in the 3 themes found in the subject, namely experience when having a broken home, experience when living with an uncle and experience when becoming an entrepreneur. Sub-themes that explain this include thinking for yourself, being independent, being highly educated, working, learning to be an entrepreneur, a trusted person in the company, background in starting a business, managing a business and managing business results. The results of the experiential learning carried out by the subject also trigger psychological aspects.